An Investigation of Surface Finish in Dry Turning - Islam, Mohammad Nazrul; Boswell, Brian (Newswood Limited, 2011)
This paper presents experimental and analytical results of an investigation of the three major cutting parameters—cutting speed, feed rate, and depth of cut—that affect the surface finish of turned parts in dry turning. A two-level, three-parameter experiment was planned using design-of-experiment methodology. The selected work materials were aluminium (AISI 6061), mild steel (AISI 1030), and alloy steel (AISI 4340). The results were analysed applying three methods—traditional analysis, Pareto ANOVA, and the Taguchi method. Subsequently, predictive models were developed for each material applying regression analysis. The results indicate that, while the feed rate has a dominant effect on surface finish, the interaction between cutting speed and feed rate also plays a major role which is influenced by the properties of work material.